UNPACKING THE INDEPENDENCE OF THE INDIGENOUS PEOPLES BILL: A CRITIQUE - Ricca Anggraeni (Sriwijaya Crimen and Legal Studies, 2025)
Although the Indigenous Peoples Bill has been included in the National Legislation Programme since 2015, it has not yet entered the discussion stage at the time of writing. The bill has not been considered a concrete necessity for indigenous peoples. Regulation of Masyarakat Hukum Adat in the form of regional regulations is sufficient to recognise their existence within Indonesian society. However, Indigenous Peoples need protection to guarantee their rights, including those relating to natural resources and land, culture, and self-determination. Therefore, what is needed is more than just administrative recognition. The aim of this paper is to criticise the stagnation of the Indigenous Peoples Bill and to promote its enactment. This paper uses the normative legal research method to achieve its objectives, namely, to criticise the stagnation of the bill due to conflicts of interest in development and the underrepresentation of indigenous peoples in the power structure.